MANAJEMEN DATA BERBASIS DATABASE: SOLUSI UNTUK PENYIMPANAN DAN AKSES DATA YANG LEBIH EFISIEN - Monica Aslyza; Muhammad Irwan Padli Nasution (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The development of information technology encourages organizations and industries to manage large amounts of data in a more efficient, secure, and structured way. Database Management System (DBMS) comes as the main solution in managing and storing data, while supporting accurate data-based decision-making process. DBMS not only acts as a storage medium, but also provides security mechanisms, integration, and controlled multi-user access. As the need for data processing efficiency increases, various modern storage methods such as cloud storage are also increasingly in demand due to their flexibility and scalability in managing digital data. This article discusses the strategic role of DBMS in modern information systems, its architecture and main components, the efficiency of data storage through various media, and its integration with cloud technology as a data management solution today. Through database-based data management, organizations can minimize redundancy, improve accuracy, and accelerate the decision-making process, both in digital and industrial business environments.